Identifying Green Bonds Impact on Company Reputation and Risk - Estiningrum, Widya; Husodo, Zaäfri Ananto (Universitas Prasetiya Mulya, 2024)
In recent years, there has been a growing awareness of the severity of climate-related risks, prompting a global imperative for environmental preservation. As a result, companies are now vital contributors to sustainability efforts, requiring them to integrate environmental, social, and governance factors into their investment and financing decisions. This paper aims to provide other researchers and stakeholders with some new ideas and a clear understanding of the important research trends in studies about how certain methods linked to issuing green bonds can impact a company's reputation and associated risk. By employing a Systematic Literature Review (SLR) and content analysis of 45 articles, the research takes a corporate-centric perspective. The findings of this paper reveal a gap in the literature concerning the direct influence of green bond issuance on company reputation and associated risks. While previous studies have explored the impact of bond issuance on various performance metrics, there remains a notable absence of detailed analysis on the relationship between green bonds and corporate reputation. By shedding light on the implications of green bond issuance for corporate reputation and risk, this research underscores the importance of integrating environmental and social considerations into strategic decision-making processes.